(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of iron deficiency anemia among chronic kidney disease patients on hemodialysis therapy. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Nephrology Unit, Institute of Kidney Diseases Hayatabad Peshawar from November 2016 to November 2017. Materials and Methods: The study was conducted at Nephrology Dialysis unit of institute of Kidney Diseases (IKD) Hayatabad Medical Complex Peshawar Pakistan. Hospital based descriptive cross-sectional study. The study duration was one year. Total sample size was 204using 15.4% prevalence of IDA in CKD, 95% confidence level 5%margin of error with the help of WHO software for sample size determination. Results: The study was conducted on 204 patients presented with CKD for dialysis. The mean age of our sample was 38.81 years with a standard deviation of 15.202. We divided the patients in 3 different age groups. Patients in age groups from 18-33 years were 42.2% of patients, in the age group 34-48 years we had 21.6% patients and in age group <=60 years we had 36.3% of patients. Iron deficiency anemia was observed in 126 (61.8) patients while 78 (38.2) patients have no iron deficiency anemia. Conclusion: Anemia is a common complication among patients with chronic kidney disease. Early detection and treatment of anemia would definitely improve quality of life and reduce the burden of care.